SWL-1 Reverses Fluconazole Resistance in Candida albicans by Regulating the Glycolytic Pathway - Li, Xiao-Ning; Zhang, Lu-Mei; Wang, Yuan-Yuan; Zhang, Yi; Jin, Ze-Hua; Li, Jun; Wang, Rui-Rui; Xiao, Wei-Lie (Frontiers in Microbiology, 2020)
C. albicans is a ubiquitous clinical fungal pathogen. Prolonged use of the first-line antifungal agent fluconazole has intensified fungal resistance and limited its effectiveness for the treatment of fungal infections. The combined administration of drugs has been extensively studied and applied. SWL-1 is a lignin compound derived from the Traditional Chinese Medicine Schisandra chinensis. In this study, we show that SWL-1 reverses resistance to fluconazole in C. albicans when delivered in combination, with a sharp decrease in the IC50 of fluconazole from >200 µg/mL to 3.74±0.25 µg/mL, and also reverses the fluconazole resistance of C. albicans in vitro, with IC50 from >200 to 5.3±0.3 µg/mL. Moreover, killing kinetics curves confirmed the synergistic effects of fluconazole and SWL-1. Intriguingly, when SWL-1 was administered in combination with fluconazole in a mouse model of systemic infection, the mortality of mice was markedly decreased and fungal colonization of the kidney and lung was reduced. Further mechanistic studies showed that SWL-1 significantly decreased intracellular ATP levels and inhibited the function of the efflux pump responsible for fluconazole resistance of C. albicans. Proteomic analysis of the effects of SWL-1 on C. albicans showed that several enzymes were downregulated in the glycolytic pathway. We speculate that SWL-1 significantly decreased intracellular ATP levels by hindering the glycolysis, and the function of the efflux pump responsible for fluconazole resistance of C. albicans was inhibited，so the fluconazole sensitive of FLC-resistant C. albicans was restored. This study clarified the effects and mechanism of SWL-1 on C. albicans in vitro and in vivo, providing a novel approach to overcoming fungal resistance.